(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Communication has been an interesting arena for the advancement of networking corporations. Data traffic on the channel has introduced various sorts of interferences both at the receiving end as well as the transmitting end. Multiple access interference (MAI) is a type of interference caused by multiple cellular users who are using the same frequency allocation at the same time. It is at Massive MIMO receiver. The encoding of the digital signal with Kasami code is applied at the transmitter of Massive MIMO and decoding is applied with Kasami code at receiver to reduce the multiple access interference.